2022
DOI: 10.7759/cureus.26638
|View full text |Cite
|
Sign up to set email alerts
|

Selective Lobar Blockade With a Bronchial Blocker in Combination With a Double Lumen Tube to Manage Refractory Hypoxemia: A Case Report

Abstract: We present the case of a 66-year-old woman undergoing right robotic thoracoscopic lower lobectomy with refractory hypoxemia. After several failed attempts to improve oxygenation, we performed lobar isolation of the middle and lower lobes on the operative side utilizing a 5 Fr Arndt endobronchial blocker in combination with an in situ left-sided double lumen endotracheal tube. Once the bronchial blocker was in place in the right bronchus intermedius, 5 cm H 2 O of continuous positive airway pressure was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Currently, most research on CPAP is conducted using a DLT; moreover, it has been concluded that a CPAP of 5 cm H 2 O can improve oxygenation 26 , 27 . Few studies have investigated the optimal CPAP administered by BB, with only a few case reports using a pressure of 5 cm H 2 O 28 , 29 ; therefore, we used a CPAP of 5 cm H 2 O in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most research on CPAP is conducted using a DLT; moreover, it has been concluded that a CPAP of 5 cm H 2 O can improve oxygenation 26 , 27 . Few studies have investigated the optimal CPAP administered by BB, with only a few case reports using a pressure of 5 cm H 2 O 28 , 29 ; therefore, we used a CPAP of 5 cm H 2 O in this study.…”
Section: Discussionmentioning
confidence: 99%